2020
DOI: 10.1002/ab.21924
|View full text |Cite
|
Sign up to set email alerts
|

The growth of gossip: Socialization of relational aggression from adolescence to emerging adulthood

Abstract: The extant literature suggests that relational aggression appears in early childhood, and gradually increases throughout adolescence. However, very little research has examined the growth of relational aggression from adolescence to emerging adulthood. In addition, research generally examines socializing factors of relational aggression, such as parenting, peers, siblings, or media in isolation. Accordingly, the aim of the current study was to examine these socializing factors conjunctively as predictors of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 74 publications
(118 reference statements)
3
6
0
Order By: Relevance
“…Consistent with other researchers examining the development of indirect aggression in similar age brackets (Cleverley et al, 2012; Coyne et al, 2020; Ehrenreich et al, 2014; Orpinas et al, 2015), and our initial prediction, we found that most children were very low or low users, who declined over time (90.8%). Although this is an encouraging result, this still leaves 9.2% of the sample, who as predicted, consistently (and increasingly) used indirect aggression from late childhood to late adolescence (see also Coyne et al, 2020). These developmental findings differ from those of physical aggression whereby almost all children (96%) desist and none increase (Nagin & Tremblay, 1999).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with other researchers examining the development of indirect aggression in similar age brackets (Cleverley et al, 2012; Coyne et al, 2020; Ehrenreich et al, 2014; Orpinas et al, 2015), and our initial prediction, we found that most children were very low or low users, who declined over time (90.8%). Although this is an encouraging result, this still leaves 9.2% of the sample, who as predicted, consistently (and increasingly) used indirect aggression from late childhood to late adolescence (see also Coyne et al, 2020). These developmental findings differ from those of physical aggression whereby almost all children (96%) desist and none increase (Nagin & Tremblay, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Longitudinal studies spanning our childhood age range of 10–18 point to a decrease in use over time, even for high users (Ehrenreich et al, 2014; Karriker‐Jaffe et al, 2008; Orpinas et al, 2015). We predicted that while most children would decrease in their use of indirect aggression over time, a small group of high stable users would be found, similar to Cleverley et al (2012) and Coyne et al (2020). As for the development of indirect aggression in early adulthood, because there is so little research to guide us, we offer no directional hypotheses other than expecting to find distinct groups of higher and lower users.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…However, the development of IA is heterogeneous. Most children manifest low-to-moderate decreasing levels of IA, but a group of them manifest high or increasing levels of IA (Boutin et al, 2017, 2021; Chen et al, 2019; Pagani et al, 2010; Vaillancourt et al, 2007), and this high use can persist into adulthood (Coyne et al, 2020; Vaillancourt & Farrell, 2021). Even if the latter are in minority, in addition to causing considerable harm to others (Casper & Card, 2017), these high users of IA are at elevated risk for future detrimental outcomes, such as anxiety, depression, delinquency, drug use, and risky sexual behaviors (Boutin et al, 2018; Card et al, 2008; Chen et al, 2019; Cleverley et al, 2012; Ehrenreich et al, 2016).…”
Section: Psychopathic Traits Dimensions and Iamentioning
confidence: 99%